Ефективність використання низькоенергоємних цементів для будівельних розчинів - Кропивницька, Т. П.; Іващишин, Г. С.; Котів, М. В.; Чекайло, М. В.; Kropyvnytska, T.; Ivashchyshyn, H.; Kotiv, M.; Chekaylo, M. (Видавництво Львівської політехніки, 2018)
Розглянуто основні принципи стратегії сталого розвитку в цементній промисловості. На прикладі ПАТ “Івано-Франківськцемент” показано, що випуск екоцементів забезпечує реалізацію в цементній промисловості прогресивних моделей раціонального використання природної сировини, палива, електричної енергії за мінімальних викидів CO2. Проведено порівняння ефективності приготування будівельних розчинів на основі портландцементів і низькоенергоємних цементів. Показано, що синергічне поєднання мінеральних добавок при суттєвому зменшенні вмісту високоенергоємної клінкерної складової в цементах дає змогу покращити технічні характеристики розчинів. Встановлено, що покращені експлуатаційні властивості кладки забезпечуються при застосуванні аерованих розчинів на основі цементу ЦБР 300. Встановлено взаємозв’язок мікроструктури і міцності цементної матриці та показана ефективність застосування комплексних модифікаторів для будівельних розчинів

The basic principles of the sustainable development strategy in the cement industry. The example of JSC “Ivano-Frankivsk Cement” shows that the production of special eco-cement provides the implementation of progressive models of rational use of natural raw materials, fuel, electric energy with the minimal CO2 emissions in the cement industry. Also it allows the implementation of the practice of clean production. The comparison of the efficiency during the preparing of building mortar based on Portland cements and low-energy cements was conducted. It is shown that a synergistic combination of mineral additives with substantial reduction of high energy-consumption clinker component in the cements allows to improve technological properties of mortars. The results of technological properties of mortar mixtures, physical and mechanical properties of building mortar based on special cement are presented. It was established that the improved operational properties of the masonry are provided by the use of modified by air-entraining admixture mortar based on cement MC 22,5 X. The interconnection of the microstructure and the strength of the cement matrix is established and the efficiency of use of complex modifiers for the mortar is shown. Physicochemical modification of mortars by complex air-entraining admixture allows to obtain highquality modified plasters with improved quality parameters.
Efficiency of use the low-energy cements for building mortars
Keywords: низькоенергоємні цементи; будівельні розчини; міцність; low-energy cements; building mortar; strength; 666.94